2020
DOI: 10.1111/are.14584
|View full text |Cite
|
Sign up to set email alerts
|

Identification and pathogenicity study of emerging fish pathogens Acinetobacter junii and Acinetobacter pittii recovered from a disease outbreak in Labeo catla (Hamilton, 1822) and Hypophthalmichthys molitrix (Valenciennes, 1844) of freshwater wetland in West Bengal, India

Abstract: The disease outbreaks in aquaculture system of wetlands are the major cause of fish mortality. Among various bacterial septicaemic diseases, fish mortality caused by Acinetobacter spp. is recently reported in different fish species. Fish disease outbreak was investigated in a wetland of West Bengal, India to identify the aetiological factors involved. The moribund fish were examined and subjected to bacterial isolation. Two bacterial causative agents were identified as Acinetobacter junii and Acinetobacter pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 35 publications
2
17
0
1
Order By: Relevance
“… Xu et al (2019 , 2020b) , using SMRT sequencing, revealed that L. parafarraginis , L. silage , L. buchneri , L. farciminis , and L. paralimentarius were the main species and predominant bacterial community in whole-plant corn silage after ensiling for 90 day. Acinetobacter species are a group of Gram-negative, strictly aerobic, non-fermenting organisms that are ubiquitous in polluted aquatic environments, sewage, vegetables, and can be pathogenic in animals and humans ( Xia et al, 2008 ; Malick et al, 2020 ). In the present study, they might have been present in the materials before ensiling, have greater acid resistance than other bacteria in silages and therefore dominated the bacterial community during aerobic exposure ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“… Xu et al (2019 , 2020b) , using SMRT sequencing, revealed that L. parafarraginis , L. silage , L. buchneri , L. farciminis , and L. paralimentarius were the main species and predominant bacterial community in whole-plant corn silage after ensiling for 90 day. Acinetobacter species are a group of Gram-negative, strictly aerobic, non-fermenting organisms that are ubiquitous in polluted aquatic environments, sewage, vegetables, and can be pathogenic in animals and humans ( Xia et al, 2008 ; Malick et al, 2020 ). In the present study, they might have been present in the materials before ensiling, have greater acid resistance than other bacteria in silages and therefore dominated the bacterial community during aerobic exposure ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…was clearly superior to the NNV group, whereas the vibrio group was enriched with Ralstonia spp., some species reported as infectious bacteria on human, which cause meningitis, respiratory infection and catheter related infection [ 94 ]. Acinetobacter spp., which are abundant in NNV, GIV and Vibrio-infected grouper, were identified as serious pathogens that could lead to major disease outbreak in Labeo catla [ 95 ]. In the Vibrio group, Ralstonia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, Plesiomonas (shigelloides) (Liu et al, 2015), Flavobacterium (columnare) (Dong et al, 2015) and Acinetobacter spp. an emerging group of freshwater fish pathogens (Malick et al, 2020). Likewise, among the detected microeukaryotic genera, there were species pathogenic to tilapia, including the parasitic ciliate Ichthyophthirius multifiliis (El-Dien and Abdel-Gaber, 2009) and two skin-targeting pathogenic oomycetes, Aphanomyces invadans (OIE, 2013) and Saprolegnia parasitica (Ellison et al, 2018) but the metabarcoding of short hypervariable regions of marker genes does not allow us to accurately assign species or strain level classifications to determine their pathogenicity.…”
Section: Clr Abundancementioning
confidence: 99%